DETECTION OF SPECIFIC SURFACTANT PROTEINS IN GASTRIC ASPIRATES FROM PREMATURELY BORN CHILDREN AFTER CORTICOSTEROID THERAPY - Vishnya Stoyanova; Asya Tsanova; Albena Jordanova; Neli Jekova; Detelina Stoichkova; Krasimira Ivanova; Emilia Hristova (Peytchinski Publishing, 2020)
Purpose: Alveolar surfactant (AS) components, including the specific surfactant proteins (SPs) SP-A, SP-B, SP-C, and SP-D, provides stability during the dynamic process of inhalation/exhalation. In prematurely born children different respiratory pathologies due to surfactant components deficiency, like Neonatal Respiratory Distress Syndrome, can be observed. Administration of corticosteroids to pregnant women at risk of preterm birth is an established intervention in clinical practice. In this study, we analyzed gastric aspirates (GAs), as alternative samples of tracheal aspirates and amniotic fluids for AS maturity determination. Samples were taken from prematurely born babies after antenatal corticosteroid therapy (CST) of pregnant women and were analyzed for the presence of specific surfactant proteins. Materials and Methods: Clinical samples of gastric aspirates were collected in the first minutes after delivery by using of a nasogastric tube and were analyzed by Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot assays for detection of SP-A, SP-B, and SP-C. Results: Our results showed the expression of different isoforms of each specific surfactant protein (SP) in all GA samples, depending on the stage of maturation. Conclusions: Our results showed that CST plays a role in AS components production and maturation. Moreover, GA can be considered as an adequate sample for assessment of surfactant maturity at birth.